Análise da agilidade em atletas de voleibol juvenil: comparação entre as respectivas posições do voleibol - SOUSA, Alan Medeiros de (2022)
Agility in volleyball athletes compared to their positions involves a crucial role in the process of physical assessment and understanding of the individual within the sport. The aim of this study was to analyze athletes' profiles in correlation with volleyball positions using physical agility valence as a parameter of comparison. This study evaluated 37 athletes, aged between 15 and 17 years, being the criterion for participation to be playing the JEP (Paraense Student Games); Agility was evaluated by the Shuttle Run test. With the results of the averages between tips (12.1s), lifters (12.6s), opposite (12.3s), libero (11.8s) and central (12, 6s) it was found that there was no statistical difference (p> 0.5) between the referent positions. In conclusion, even being an advanced maturation age, athletes should not be specified within the youth category in physical positions using agility as a variable.